(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The artistic thinking of a nation is defined by the intellectual image of its true sons and daughters. Creativity is the understanding of the world and existence through beautiful thinking, feelings, and perception. In order to grasp the essence of creativity and its divinity, the artist must have a high level of perception of the world.